Food Nutrients and Bioactive Compounds for Managing Metabolic Dysfunction-Associated Steatotic Liver Disease: A Comprehensive Review - Dungubat, Erdenetsogt; Fujikura, Kohei; Kuroda, Masahiko; Fukusato, Toshio; Takahashi, Yoshihisa (Nutrients, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) and its progressive form, metabolic dysfunction-associated steatohepatitis (MASH), are growing global health concerns. However, pharmacological therapies for MASLD/MASH have not yet been established. Dietary interventions and their bioactive components have been explored as strategies to mitigate MASLD and MASH progression. Although specific nutrients and bioactive compounds have exhibited potential therapeutic benefits, they also exacerbate adverse outcomes. In this comprehensive review, we synthesize the protective and exacerbating or sometimes dual effects of key macronutrients, including fatty acids (saturated, unsaturated, and trans fats) and carbohydrates (fructose, glucose, and sucrose), and bioactive compounds and micronutrients, in the context of MASLD management. The evidence suggests that coffee-derived compounds, such as caffeine and chlorogenic acid, may attenuate liver injury. However, the effects on MASLD severity are inconsistent. Diets high in saturated fatty acids exacerbate MASLD pathogenesis, whereas moderate intake (7–10% of total energy) may confer metabolic benefits. Other bioactive compounds and micronutrients have been explored for their diverse roles in hepatic lipid metabolism and insulin sensitivity. Although current evidence supports the therapeutic potential of specific dietary nutrients and bioactive compounds in the management of MASLD, inconsistencies in results highlight the need for more robust, well-controlled studies, including clinical trials, to clarify the preventive and therapeutic standards for balanced food interventions in MASLD management. In particular, well-designed clinical trials are necessary before clinical application. Although this is a narrative review and the literature retrieval may be biased, we covered a wide variety of substances.